Valve Setting Using Fuzzy Logic Method To Control Main Engine Coolant Flow - suharso, didik dwi; Syafi'i, Imam; nugroho, Anicitus agung (NAROTAMA UNIVERSITY, 2023)
The main objective of this research is to improve the operating efficiency and performance of ship main engines by optimizing coolant flow. Improper coolant flow can cause excessive temperature rise in the engine, which in turn can reduce engine life and efficiency. In this research, the coolant flow control system is implemented using the fuzzy logic method. Fuzzy logic allows modeling that is more adaptive to parameter variations and uncertainties in the operational environment. Fuzzy rules are developed based on practical knowledge of experts and operational data related to the host machine. The test was carried out through a simulation using a water flow control circuit that supplies the coolant to the ship's main engine with the main components being an ESP32 microcontroller chip and three DS18B20 temperature sensors. The results of this research show that the use of fuzzy logic in regulating coolant flow is able to provide a faster and more accurate response to changes in engine operational conditions. This has the potential to increase cooling efficiency and prevent engine over-temperatures, which can ultimately increase the overall service life and performance of the host engine. The practical implications of the results of this research can be applied in the development of more intelligent and adaptive control systems for various types of host machines, with the potential to increase operating efficiency and reduce the risk of damage due to excessive temperatures